Conduction mechanism investigation in YCa2Cu3Oδ colossal permittivity ceramics - Wael Chouk; Mohamed Annabi; Mouldi Zouaoui (Results in Physics)
Sol-gel synthesized YCa2Cu3Oδ ceramic exhibits giant permittivity εr′≈104, low loss tanδ0.3, and high stability over frequency and temperature. XRD revealed a tetragonal phase (P4/mmm). XPS confirmed high oxygen vacancy density. The structural heterogeneity, shown by SEM, between neighboring grains results from Schottky barrier formation at the grain boundaries, potentially explaining the TCR phenomenon. Magnetic analysis showed paramagnetism. Electrical property investigation revealed an insulating-to-metallic phase transition with temperature, associated with changing conduction mechanisms. Paramagnetic-insulating behavior at higher temperatures is linked to thermal activation, while electron scattering contributes to paramagnetic-metallic conduction at lower temperatures. The resistivity behavior follows the percolation model, providing insights into the interplay between conducting and insulating phases, relevant for optimizing perovskite-based materials in electronics and energy storage.